Fifty, fifty [large type] - Patterson, James, 1947-; Fox, Candice (Patterson, James, 1947- Detective Harriet Blue, 2018)
Sam Blue stands accused of the brutal murders of three young students, their bodies dumped near the Georges River. Only one person believes he is innocent: his sister, Detective Harriet Blue. But Harry's outburst at her brother's trial earns her a reassignment-- to the Outback. With no choice but to leave Sam's case alone, she relocates to Last Chance Valley, population 75, where a diary found on the roadside outlines a shocking plan: the massacre of the entire town. And the first killing, shortly after Harry's arrival, suggests the clock is already ticking.